How to Build a Complex, Functional Propeller Protein, From Parts. Issue 4 (April 2016) - Clark, Patricia L.
Abstract : By combining ancestral sequence reconstruction and in vitro evolution, Smock et al. identified single motifs that assemble into a functional five-bladed β-propeller, and a likely route for conversion into the more complex, extant single chain fusion. Interestingly, although sequence diversification destabilized five-motif fusions, it also destabilized aggregation-prone intermediates, increasing the level of functional protein in vivo .